รูปแบบการมีส่วนร่วมของชุมชนในการป้องกันและแก้ไขปัญหาเกมออนไลน์ ที่มีผลต่อเยาวชนไทย : กรณีศึกษาชุมชนสีคาม กรุงเทพมหานคร - มัชฌิมา, ปริศนา; ปั้นตระกูล, สายสุดา; เผือกคง, กาญจนา (Journal of Multidisciplinary in Social Sciences, 2013)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาพฤติกรรมการเล่นเกมออนไลน์ของเยาวชนไทย 2) ศึกษาปัญหา ผลกระทบและแนวทางแก้ไขปัญหาที่เกิดจากเกมออนไลน์ และ 3) เพื่อสร้างรูปแบบการมีส่วนร่วมของชุมชน ในการป้องกันและแก้ไขปัญหาเกมออนไลน์ที่มีผลต่อเยาวชนไทย: กรณีศึกษาชุมชนสีคาม กรุงเทพมหานคร ประชากร ที่ใช้ในการศึกษา คือ คณะกรรมการบริหารชุมชน เจ้าหน้าที่ศูนย์เยาวชนสวนอ้อย สมาชิกในชุมชน ซึ่งแบ่งเป็นกลุ่มผู้ใหญ่ และกลุ่มเด็กและเยาวชน รวมทั้งหมดจำนวน 796 คน เครื่องมือที่ใช้ในการวิจัยครั้งนี้ คือ แบบสอบถาม แบบวัดพฤติกรรมการติดเกม แบบสัมภาษณ์ การจัดสนทนากลุ่ม และแบบประเมินผลโครงการ ผลการศึกษาพบว่า 1) พฤติกรรมการเล่นเกมออนไลน์ของเยาวชนไทย พบว่า เด็กและเยาวชนมีพฤติกรรมชอบเล่นเกมประเภทแอ็คชั่น/ต่อสู้ โดยเฉพาะเด็กชาย ที่มีอายุเฉลี่ยระหว่าง 11-15 ปี โดยชอบไปเล่นเกมที่ร้านเกม เนื่องจากมีเพื่อนมาก โดยเด็กจะเล่นเกมในวันเสาร์-อาทิตย์ ประมาณ 3 ชั่วโมง ซึ่งเด็กได้รับค่าใช้จ่ายจากผู้ปกครองเฉลี่ยวันละ 45-50 บาท/วัน โดยนำไปเล่นเกมวันละ 30 บาท เด็กจะเล่นเกมกับเพื่อนบ้านเป็นประจำ ซึ่งเด็กเห็นว่าเกมมีประโยชน์ในการช่วยฝึกความจำและสมาธิ ส่วนสาเหตุหลักที่ไปเล่นเกมเพราะเหงาและอยากมีเพื่อน เครียดจากที่บ้าน พ่อแม่ชอบตำหนิโดยไม่มีเหตุผล รวมถึงในชุมชนมีที่เล่นไม่เพียงพอ สิ่งที่เด็กอยากให้มีมากที่สุดในชุมชน คือ ลานกีฬา 2) ปัญหาและผลกระทบและแนวทางแก้ไขปัญหาที่เกิดจากที่เกิดจากเกมออนไลน์ ปัญหาและผลกระทบ ด้านอารมณ์ พบว่า ไม่พอใจเมื่อผู้ปกครองไม่ให้เล่นเกม ด้านสังคม พบว่า ชอบอยู่คนเดียว และด้านการเรียน พบว่า เด็กง่วงนอนในเวลาเรียน ในส่วนของผู้ปกครอง พบว่า ผู้ปกครองส่วนใหญ่ไม่ทราบว่าบุตรหลานชอบเล่นเกมประเภทใด และไม่มีการกำหนดกติกาสำหรับการเล่นเกม ทั้งในเรื่องของเงินและเวลาที่ใช้ไปกับการเล่นเกม ส่วนผลกระทบที่เกิดจากเกมออนไลน์ด้านเศรษฐกิจ พบว่า การเล่นเกมทำให้เสียเงินโดยเปล่าประโยชน์ ด้านสังคม พบว่า ก่อให้เกิดปัญหาการลักทรัพย์ และด้านจริยธรรม พบว่า เด็กขาดความรับผิดชอบในการเรียน สำหรับแนวทางในการป้องกันและแก้ไขปัญหาเด็กติดเกม จากผลการสัมภาษณ์ผู้ปกครอง พบว่า พ่อแม่ต้องดูแลไม่ให้เด็กมีเวลาว่างมากเกินไป ต้องปรับวิธีการ เลี้ยงลูก และชุมชนต้องช่วยกันสอดส่องดูแลพฤติกรรมของเด็กอย่างจริงจัง 3) รูปแบบการมีส่วนร่วมของชุมชนในการป้องกันและแก้ไขปัญหาเกมออนไลน์ที่มีผลต่อเยาวชนไทย: กรณีศึกษาชุมชนสีคาม กรุงเทพมหานคร ประกอบด้วยปัจจัยหลัก 3 พ คือ “เพื่อน” ที่มีบทบาทอย่างมากในการชักชวนเพื่อนที่ชอบเล่นเกม ให้ไปทำกิจกรรมสร้างสรรค์อื่นๆ “พ่อแม่” ที่มีบทบาทสำคัญในการดูแลลูก และ “พื้นที่” ในที่นี้หมายถึงพื้นที่ที่เหมาะสมสำหรับการทำกิจกรรมสำหรับเด็กในชุมชน คําสําคัญ: ภัยออนไลน์ เกมออนไลน์ การมีส่วนร่วมของชุมชน Abstract The purposes of this research were 1) to study the online game playing behaviors of Thai youths; 2) to study problems, impacts, and guidelines for solving the online game problems; and 3) to create a model of community participation in prevention and solution of online game problems affecting Thai youths based on a case study of the Seekam Community in Bangkok Metropolis. The populations of this study comprised the administrative committee members of Seekam Community, the officers and staff of Suan Oi Youth Center, and 796 members of Seekam Community divided into the adult and youth groups. Research data were collected via the use of questionnaires, interview forms, focus group discussion, and a project evaluation form. The research findings were as follows: 1) Regarding online game playing behaviors of Thai youths, it was found that the youths likes to play action/fighting games, especially boys with averaged age between 11-15 years. They liked to play at online game shops because they could join with friends and play together. They usually played games in the weekend for about 3 hours a day. They received the averaged allowance of 45 - 50 baht per day from their parents, and spent 30 baht to play on online games with friends. In their opinions, online games helped them to increase their memory and concentration. The major factors that caused them to go out and play games were their loneliness, the need to have friends, the stress from the family, the scolding from their parents, and insufficiency of playing grounds in the community. The thing that they wanted to have most in their community was the sports area. 2) Regarding the problems, impacts, and guidelines for solving the online game problems, for problems and impacts on the youths’ emotion, it was found that the youths were not satisfied when parents did not allow them to play the online games; for the problems and impacts on their social behavior, it was found that they liked to be alone; for the problems and impacts on their study, it was found that they often were sleepy during class sessions; as for the part of the parents, it was found that the majority of parents did not know what online games their children liked to play, and they did not set up any regulations for their children to play games including on the matters of money allowance and time allowance for game playing; as for the economic impact caused by playing games, it was found that game playing resulted in useless additional expense; for the social impact, it was found that game playing caused theft problems; for the moral impact, it was found that game playing caused the youths to be irresponsible in their study; as for guidelines for prevention and solving the online game problems based on results of interviewing parents, the parents should make sure that their children do not have too much free time, they should modify their method of child rearing, and the community should more seriously help in monitoring behaviors of youths. 3) Regarding the model of community participation in prevention and solution of online game problems based on the case study of Seekam Community, it was proposed that the model should be composed of 3P components, namely, “Partners” that play important roles in persuading youths who like to play online games to be engaged in other creative activities; “Parents” that play important roles in rearing and taking care of their children; and “Place” that is the appropriate playground area provided by the community for youths to play outdoor games. Keywords: Online danger, Online game, Community participation